71 Do robotic-supported prostatectomies provide superior clinical outcomes over traditional techniques? application of a novel, quantitative approach for evaluating clinical evidence. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Rutkowski, Michal; Jasonek, Dariusz; Kalinowska, Agnieszka; Cekala, Eryk; Iwanow, Dariusz; D'Agostino, Gina; Liu, Ray
Abstract : Objectives: Robotic surgeries have the potential to reduce the difficulty of complex laparoscopic procedures by providing more precise dissections, leading to better preservation of functional structures and therefore better outcomes. While a robotic approach is said to be beneficial, its actual performance requires a scientific evidence-based evaluation. In this analysis, we explore all relevant studies comparing robotic-assisted radical and simple prostatectomies (RARP and RASP, respectively) to laparoscopic radical and simple prostatectomies (LRP and LSP) and traditional open radical and simple prostatectomies (ORP and OSP). The numerous published studies on these comparisons reach conflicting conclusions regarding the benefit of robotic-assisted surgeries. Therefore, it is essential to apply a systematic approach that uses quantified objective measures to evaluate the entire landscape of evidence. Method: A comprehensive literature search of multiple databases was performed for digitally accessible full-text articles and abstracts published between 2011 and 2018. Studies comparing directly robotic-assisted prostatectomies with laparoscopic and/or open surgeries were included. With the support of a tool called EvidenceEngineTM, the studies were collected and analysed based on their directional conclusions and level of merit. This level of merit is quantified into a score based on the factors of study design, population size, potential conflict of interest, publication date and peer review status. An analysis of the clinical outcomes results was then performed considering following head-to-head comparisons: RARP vs LRP, RARP vs ORP, RASP vs LSP and RASP vs OSP. Their results were then compiled with each study's conclusion weighted by its merit to arrive at an Overall Score (OS) for each head-to-head comparison. Results: The evidence comparing RARP and LRP resulted in an OS of 4.2/10 in support of the robotic technique, with benefits that include functional outcomes (higher urinary continence and potency), lower blood loss and transfusion rate, and shorter length of hospital stay (LOS). In the comparison between RARP and ORP, the OS was 2.7/10 in weak support of the robotic technique, with benefits of lower blood loss and transfusion rates, shorter LOS, and faster recovery of functional outcomes, but longer operation times. In the comparison between RASP and LSP, the OS of 0.1/10 in opposition to the robotic technique reveals that there is no meaningful difference between the two approaches. Finally, the evidence on RASP vs OSP concluded an OS of 4.0/10 in support of the robotic-assisted approach, with lower transfusion prevalence and shorter LOS, but longer operation times. Conclusions: In the case of radical and simple prostatectomies, the analysis concludes that the robotic-assisted approach for radical prostatectomies can be beneficial over conventional techniques. On the other hand, for simple prostatectomies, the robotic-assisted approach is favourable to OSP but showed no difference in outcomes in comparison to LSP. While robotic-assisted surgeries have numerous potential benefits over traditional approaches, a systematic, quantified evaluation of the evidence surrounding these surgeries may reveal unique insights that are very valuable for health system decision-making.